2015
DOI: 10.5152/akd.2014.5169
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of mean platelet volume in patients undergoing elective percutaneous coronary intervention

Abstract: Objective:We sought to determine the role of mean platelet volume (MPV) for predicting long-term outcomes of elective percutaneous coronary intervention (PCI).Methods:On the basis of retrospective cohort study, we collected characteristics of 680 patients undergoing elective PCI from October 2005 to August 2010. The patients who had preoperative MPV were assessed for developing major adverse cardiac events (MACE) during 1-year follow-up. They were categorized into two groups including MPV <9.6 fL (n=89) and MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…found that the best MPV cutoff point was 9·25 fL with sensitivity and specificity of 79% and 38%, respectively. This elevated MPV value was the best predictor of MACE at 1‐year follow‐up (OR = 11·3, 95% CI 2·4‐51·9, P = 0·002) .…”
Section: Discussionmentioning
confidence: 92%
“…found that the best MPV cutoff point was 9·25 fL with sensitivity and specificity of 79% and 38%, respectively. This elevated MPV value was the best predictor of MACE at 1‐year follow‐up (OR = 11·3, 95% CI 2·4‐51·9, P = 0·002) .…”
Section: Discussionmentioning
confidence: 92%
“… 8) 9) Mean platelet volume (MPV), an index of platelet activation, has been shown to be associated with adverse cardiovascular outcomes. 10) MPV was found to be elevated in SCF cases compared to normal ones. 11) Platelet distribution width (PDW) is found to be increased during platelet activation.…”
Section: Introductionmentioning
confidence: 82%
“…The mean platelet volume, a platelet activation marker, is a widely available and easily measured hematologic test in a complete blood cell count test [7], and the elevated one has been demonstrated to be associated with diabetes mellitus, hypertension, hypercholesterolemia, and obesity [7]. In addition, it has been found to be a diagnostic and prognostic marker in patients with ACS or those undergoing percutaneous coronary intervention [15][16][17]. However, in a prospective study, no relationship was found between increased baseline mean platelet volume and the clinical outcomes of patients undergoing elective angioplasty, but increases in postoperative serial measurements were associated with higher mortality rate instead [18].…”
Section: Discussionmentioning
confidence: 99%